Let f(x) and g(x) be two functions such that
lim(x→p) f(x) and lim(x→p) g(x) exists then **Sum Rule:**lim(x→p) [f(x) + g(x)] = lim(x→p) f(x) + lim(x→p) g(x)**Product Rule:**lim(x→p) [f(x)g(x)] = [lim(x→p) f(x)][lim(x→p) g(x)]**Reciprocal Rule:**lim(x→p) [1/f(x)] = 1/[lim(x→p) f(x)] provided lim(x→p)f(x))≠0**Constant function rule:**lim(x→p)k=k**Identity function rule:**lim(x→p)x=p
Theorem: If lim(x→p) f(x)= L and lim(x→p) g(x)= M then L = M Theorem: Let f,g and h be three functions defined on the interval I may or may not containing p, i) f(x)≤g(x)≤ h(x) ∀x ∈ I ii) lim(x→p) f(x) = L = lim(x→p) h(x) exists then lim(x→p) g(x) exist and is equal to L. This theorem is called Sandwich theorem or Squeeze theorem |

BSc Students > Single Variable Calculus >